A bio-inspired soft-rigid hybrid actuator made of electroactive dielectric elastomers. (December 2020) - Liu, Lei; Zhang, Junshi; Luo, Meng; Chen, Hualing; Yang, Zhichun; Li, Dichen; Li, Pengfei
Highlights: A soft-rigid hybrid actuator (SRHA) is developed based on fiber-reinforced dielectric elastomers (DEs) and a skeleton backbone system. Effect of distribution of skeletons on the SRHA is studied through both experiments and FEM simulations. The fabricated SRHA is discovered to be with two actuation modes: the voltage control mode and the pressure control mode. The variable stiffness unit (VSU) is designed for the SRHAs to ensure the stiffness maintaining capability. Abstract: In this article, inspired by biological structures, we develop a soft-rigid hybrid actuator (SRHA), based on fiber-reinforced dielectric elastomers (DEs) and a skeleton backbone system. The skeleton backbone is designed by mimicking the septa-muscle structure of earthworms. The fiber-reinforced DEs are conceived from the unidirectional and antagonistic deformation of natural muscles. Effect of distribution of skeletons on the SRHA is firstly studied through both experiments and FEM simulations. Besides, the fabricated SRHA is discovered to be with two actuation modes: (a) the voltage control mode, which is suitable for small deformation and accurate tuning; (b) the pressure control mode, which can be utilized for high output force and coarse tuning. Moreover, upon the critical pneumatic pressure (a prime trigger which highly relies on the distribution of skeletons), the pressure control mode can evolve to an enhancement mode by harnessing the buckling instability. Furthermore, in this enhanced mode, the electric power reduces to an ultra-low threshold for DEAs (even less than 2000 V), and hopefully degrades into a direction guiding disturbance. On the other hand, to ensure the stiffness maintaining capability, based on the fiber jamming mechanism, the variable stiffness unit (VSU) is designed for the SRHAs by absorbing the inspiration from the protective constraint mechanism of ligament-bone system. Remarkable stiffness maintaining capability of SRHA is experimentally proved to carry more than 20 times loads than its own weight. This proposed SRHA holds a great promise for application in continuum soft robotics explorations. Graphical abstract: In this article, inspired by biological structures, we develop a soft-rigid hybrid actuator (SRHA), based on fiber-reinforced dielectric elastomers (DEs) and a skeleton backbone system. The skeleton backbone is designed by mimicking the septa-muscle structure of earthworms. The fiber-reinforced DEs are conceived from the unidirectional and antagonistic deformation of natural muscles. Effect of distribution of skeletons on the SRHA is firstly studied through both experiments and FEM simulations. On the other hand, to ensure the stiffness maintaining capability, based on the fiber jamming mechanism, the variable stiffness unit (VSU) is designed for the SRHAs by absorbing the inspiration from the protective constraint mechanism of ligament-bone system Image, graphical abstract .